OSN-Tagging Scheme and Its Steganalysis Realizing Using Machine Learning Model - Lekshmi R.Nair (International Journal of Engineering and Management Research, 2023)
Steganography is a type of art and steganalysis is that art fining.In this work we propose a machine learning model for steganaysis. An SVM(Support Vector Machine) –Classification model. Testing the model with the help of OSN(Online Social Network)-Tagging scheme. Facebook was selected from all amoung the OSN for OSN-Tagging. Machine classify the steg-algorithm’s accuracy in percentage.